(untitled) (Patan Pragya, 2022)
This article addresses the issue of increasingly outspoken about environmental problems in American Southwest as portrayed in Rudolf Anaya’s Devil Deer. Impact of toxicity in the environment and the health of flora and fauna are some of the serious issues. Likewise, with the establishment of Los Alamos National Laboratory (LANL)-national’s military industrial complex, the radioactive rays and carcinogenic chemicals though LANL which spread toxicity that has contaminated all the beings. The natural healthy, robust beings have become poisonous, and like mutilated devil. To the flora and fauna the traditional autumn hunting “ritual” of Chicanos community has been also disrupted. From the eco-critical perspective, it is injustice to all the living creatures and plants by the acts of humans. Because of the human’s mastery exploitation, environmental apocalypse has taken place. Besides, plants as well as all living creatures are in en-dangerous situation since people are supposed to be the master of environment. Their hegemony, subjugation, exploitation are greatly on the nature so that the direct effect has been seen in the buck as depicted in the text. This article is a contribution to the existing knowledge on the perilous impact of human carelessness on the entire ecological system.